Structure Requirements for 4-Aryl-4H-Chromenes as Apoptosis Inducers Using 3D QSAR Methods and Docking Studies - Liu, Zhen; Li, Yan; Ren, Hong; Zhang, Shuwei; Wang, Yonghua; Li, Guohui; Yang, Ling (Asian Journal of Chemistry, 2012)
Presently, a computational study based on the combinational use of 3D-quantitative structureactivity relationship analyses (QSAR) methods including both the comparative molecular field analysis (CoMFA) and comparative molecular similarity analysis (CoMSIA) approaches and molecule docking was conducted on a series of 124 types of 4-aryl-4H-chromenes of 24 diverse structural scaffolds as promising novel apoptosis inducers, with purpose to explore the requisite structural features influencing their activity of caspase-3 activation in human breast tumor cells. The obtained 3D-QSAR models exhibited proper reliability and predictivity, where the optimal comparative molecular field analysis and comparative molecular similarity analysis ones gave leave-one-out cross-validation coefficient Q2 of 0.508 and 0.477, conventional cross-validation coefficient R2ncv of 0.888 and 0.816 for the training set and predictive correlation coefficients R2pre of 0.604 and 0.150 for the independent test set, respectively. Analyses of the derived contour maps reveal that steric substituents at positions 4, 9-13, 15 and 16 favour the apoptosis inducing activity and electron-withdrawing groups at 6 and 10 positions or electron-donating groups at position-7 enhance the activity. Further docking study validates that 4-aryl-4H-chromenes bind at the colchicine site of tubulin and several hydrogen bonds serve to stabilize the ligand-tubulin complex. These models and the derived information, would be of value for further exploration of the apoptosis inducing mechanism and the screening of novel potent chromene-based apoptosis inducers.